Charting a roadmap towards membership and formal voice in global bioethics standard- setting: Health research and the case of the International Council on Harmonisation. (June 2018) - Flear, Mark
The United Kingdom's (UK's) imminent departure from the European Union (EU) has a further but usually overlooked consequence: The UK will also be leaving the various global fora where it has been represented with other Member States of the EU. In many cases, the UK will still have to comply with the global regulatory tools, including norms and standards, made by these fora. The UK's departure from the EU thus raises the more general question of how those formally outside the fora that set global norms and standards can navigate membership procedures in order to become involved in setting them. This article focuses on the example of the International Council on Harmonisation (ICH) and its work in harmonizing good clinical practice (GCP) in relation to clinical trials for pharmaceuticals. By reference to this example, the article underlines the importance of the ICH to global standard-setting for GCP and the importance of engagement in this forum by those that do not have a formal role in setting the standards, but that must abide by them nonetheless if they are to trade globally. Subsequently, the article explains the formal procedures for membership and involvement in standard-setting. In doing so, the article aims to provide a roadmap towards membership and a say in global standard-setting.